2022
DOI: 10.3389/fendo.2022.850334
|View full text |Cite
|
Sign up to set email alerts
|

Perirenal Fat Thickness: A Surrogate Marker for Metabolic Syndrome in Chinese Newly Diagnosed Type 2 Diabetes

Abstract: ObjectiveIncreasing evidence suggested that perirenal fat thickness (PrFT) was associated with metabolic risk factors. This study aimed to assess the association between PrFT and metabolic syndrome (MetS) in Chinese newly diagnosed type 2 diabetes (T2DM), further evaluating the ability of PrFT in identifying MetS.MethodA total of 445 Chinese newly diagnosed T2DM were enrolled in this study from January to June 2021. Demographic and anthropometric information were collected. PrFT was evaluated by CT scan on Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In the subgroup analysis, Pearson correlation analysis showed that the relationship between PrFT and PnFT and SUA in males was stronger than that in females. While another study conducted by Guo et al presented a higher correlation between PrFT and SUA in females [ 24 ].That study enrolled patients with newly diagnosed T2DM and with mean age of 52.5 ± 8.2 years, which may explain the contrary results. In addition, we also found that the relationship between PrFT and PnFT and SUA was not significant in patients with reduced renal function.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the subgroup analysis, Pearson correlation analysis showed that the relationship between PrFT and PnFT and SUA in males was stronger than that in females. While another study conducted by Guo et al presented a higher correlation between PrFT and SUA in females [ 24 ].That study enrolled patients with newly diagnosed T2DM and with mean age of 52.5 ± 8.2 years, which may explain the contrary results. In addition, we also found that the relationship between PrFT and PnFT and SUA was not significant in patients with reduced renal function.…”
Section: Discussionmentioning
confidence: 98%
“…The main finding of our study was that the PrFT was independently and positively associated with SUA level in patients with T2DM. As previous studies reported, PrFT and PnFT were positively associated with SUA respectively in diabetic patients [ 19 , 24 ], while some confounders were not adjusted. Similarly, Lamacchia et al and Giulio et al reported that para-and perirenal fat thickness was significantly and positively associated with SUA in diabetic patients and hypertensive patients respectively [ 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46,47 More recently, the perirenal fat thickness was recognized as a surrogate marker of metabolic syndrome in T2DM patients. 48 Irrespective of morphological changes in renal compartment volumes and RSF, elevated lipid deposition in renal parenchyma was observed in both clinical and preclinical studies at early stage DKD. These findings suggest that fat-sensitive MRI biomarkers such as Dixon quantified proton density fat fraction (PDFF) might be early indicators for the timely clinical intervention of DKD.…”
Section: Mri Markers Of Renal Morphologymentioning
confidence: 94%
“…Recent studies suggest that perirenal fat thickness (PrFT) measured by ultrasonography showed excellent consistency compared with MRI and can serve as a simple and reliable imaging indicator of visceral obesity in the metabolic syndrome; And perirenal fat was significantly associated with the levels of gamma-glutamyl transferase, fasting plasma glucose, waist circumference, and metabolic syndrome. 12 , 13 However, the relationship between PrFT and vitamin D status is unclear. Therefore, the aim of this study is to investigate the relationship between PrFT and serum 25-hydroxy vitamin D [25(OH)D] in MS patients.…”
Section: Introductionmentioning
confidence: 99%